TEACHERS' TRANSLANGUAGING PRACTICES: A COMPARATIVE STUDY OF GRADE 7 AND 9 ENGLISH TEACHERS AT JUNIOR HIGH SCHOOL 1 SEMARANG - Atilla Eka Aprilia; Zulfa Sakhiyya (Universitas Suryakancana, 2026)
This paper examines the translanguaging practices of English teachers in Grade 7 and Grade 9 classrooms at Junior High School 1 Semarang. Translanguaging refers to the flexible use of multiple languages in communication and learning. This study investigates how teachers switch between English and Indonesian during instruction to explain lessons, give instructions, manage the class, and provide feedback. Using qualitative methods, including classroom observations and semi-structured interviews, this research compares translanguaging patterns between the two grade levels. Findings show that translanguaging was used more frequently and intensively in Grade 7 classrooms to support basic comprehension and classroom management, whereas in Grade 9 classrooms it was applied more selectively and strategically to explain complex concepts. The comparison highlights how teachers adapt their translanguaging practices to students' English proficiency levels and learning needs. Grade 7 students, with limited English proficiency, require more L1 support, whereas Grade 9 students benefit from selective translanguaging for complex content. This study suggests that translanguaging functions as an adaptive pedagogical strategy in EFL classrooms when applied purposefully. Keywords: Comparative Study, English Language Teaching, Grade 7, Grade 9, Translanguaging